DEVELOPMENT OF NATIONAL DANCE ART - Rasulova Rukhshona Maksudjon kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article provides theoretical information about the art of dance and guidelines for the development of Uzbek national dance art.